Loss of Chromium(III) From Mixed Cr(III), Fe(III) Serum Transferrins. (14th June 2022) - Vincent, John; Keith, Darby; Graham, Dylan; Edwards, Kyle
Abstract: Objectives: Transferrin, Tf, the protein that transports iron as Fe(III) from the blood to the tissues via endocytosis, is believed to also transport chromium(III), Cr(III). Under physiological conditions, Tf binds and releases Cr(III) rapidly from Cr(III)2 -Tf; however, the major form of Tf in the bloodstream is mono-ferric Tf. Given the low concentration of Cr(III) in the bloodstream, the form of Cr(III)-containing Tf that is transported is probably monochromic, monoferric-Tf (Cr(III), Fe(III)-Tf). Given that Tf has two specific metal-binding sites, one in both its C-terminal and the N-terminal lobe, two forms of Cr(III), Fe(III)-Tf can form. The loss of Cr(III) from both forms of Cr(III), Fe(III)-Tf has been examined for the first time. Methods: Cr(III), Fe(III)-Tf with Cr(III) in the C-lobe was prepared by adding CrCl3 to N-lobe monoferric Tf in deionized H2 O at pH 7.5 containing ∼20 mM bicarbonate. Cr(III), Fe(III)-Tf with Cr(III) in the N-lobe was prepared by adding 1 equivalent of Fe as ferrous ammonium sulfate to Cr(III)2 -Tf in 0.1 M HEPES buffer solution with 25 mM bicarbonate at pH 7.4. To examine the release of Cr(III), the pH of solutions of Cr(III), Fe(III)-Tf were acidified from pH 7.4 to pH 5.5. After time intervals, aliquots were removed and frozen for analysis by electron paramagnetic resonance (EPR) spectroscopy, which can distinguish aquated Cr(III) and Cr(III) bound to each of the two metal binding sites of Tf. Results: The acidification of solutions of Cr(III), Fe(III)-Tf's in 100 mM HEPES and 25 mM bicarbonate solution, pH 7.4 to pH 5.5 resulted in a rapid loss of Fe(III) followed by a slower loss of Cr(III). The loss of Cr(III) from the Cr(III), Fe(III)-Tf with Cr(III) in the C-lobe is about 4 times faster than that from the same site in Cr(III)2 -Tf. For the other site, the Cr loss is about 28 times faster. Thus, having one site vacant from the loss of Fe(III) leads to faster loss of Cr(III) from both lobes, suggesting Cr(III) loss is cooperative. Conclusions: Mixed-metal Cr(III), Fe(III) Tf's loose Cr(III) for both metal binding sites in similar fashions to Cr(III) losses from Cr(III)2 -Tf. Cr(III) is probably transported as mixed Cr(III), Fe(III)-Tf's. Funding Sources: The University of Alabama Bioinorganic Chemistry of Chromium Research Fund.